Penerapan Teknik Partisi Langkah Kuda Papan Catur pada Pelabelan Super (a,d)-P_2 (▷) ̇ H-Antimagic Total Covering Sebarang Dua Graf dan Aplikasinya - A H Rahmatillah; I H Agustin; Dafik Dafik (CGANT JOURNAL OF MATHEMATICS AND APPLICATIONS, 2022)
Let  be a finite collection of simple, nontrivial and undirected graphs. A graph  is as antimagic total covering if there is bijectif  function  for every subgraph in which isomorfic to  and the total  weight,  form arithmetic sequence , in which a,b are integers and n is a number of graph cover of which the result of total comb product operation. A antimagic total covering  is as "super" if smallest label is used for vertex labelling. The way for labelling a graph this time, using a knight move partition techniques application. The graph use total comb product operation . Take a copy of  and a number  of , then put the  copy of -sequence in graph vertex  to -sequence vertex of  and put the  copy of -sequence in graft edge  to -sequence edge of  is definition of total comb product. In this article, will be investigated about Knight Move Partition Techniques Application in Labelling Super Antimagic Total Covering for Any Two Graphs and Its Application (in Constructing Ciphertext).